Perioperative myocardial injury and infarction after noncardiac surgery: a review of pathophysiology, diagnosis, and management - Kashlan, Besher; Kinno, Menhel; Syed, Mushabbar (Frontiers in Cardiovascular Medicine, 2024)
Perioperative myocardial injury is a relatively common complication after noncardiac surgery associated with significant morbidity and mortality. It is frequently driven by physiologic factors such as hypotension, tachycardia, and anemia. Diagnosis of perioperative myocardial injury after noncardiac surgery is based on elevated cardiac troponin levels, greater than the 99th percentile of the assay's upper reference limit within 30 days of surgery. Perioperative myocardial injury is further classified into non-ischemic and ischemic based on the underlying pathophysiology. Ischemic injury, also called myocardial injury after non-cardiac surgery (MINS), is further classified into perioperative myocardial infarction or myocardial injury without infarction. Classifying perioperative myocardial injury further is particularly important for clinical management and prognosis. MINS—with or without infarction—is independently and strongly associated with short- and long-term mortality. Compared to nonoperative myocardial infarction, perioperative myocardial infarction carries an increased risk of adverse outcomes including all-cause mortality. Preventative measures include a thorough preoperative risk assessment, risk factor optimization, and avoidance of intraoperative mismatch of myocardial oxygen supply and demand. Surveillance of patients at higher risk of cardiovascular complications is warranted and can lead to early recognition, closer monitoring, and appropriate management. This review will provide a framework for understanding perioperative myocardial injury and highlight the contemporary literature addressing its diagnosis and management.